The European Medicines Agency approval of 5-aminolaevulinic acid (Ameluz) for the treatment of actinic keratosis of mild to moderate intensity on the face and scalp: Summary of the scientific assessment of the Committee for Medicinal Products for Human Use. (October 2014) - Tzogani, Kyriaki; Straube, Myrjam; Hoppe, Ute; Kiely, Peter; O'Dea, Geraldine; Enzmann, Harald; Salmon, Patrick; Salmonson, Tomas; Pignatti, Francesco
The European Commission has recently issued a marketing authorisation valid throughout the European Union for 5-aminolaevulinic acid (Ameluz). The decision was based on the favorable opinion of the CHMP recommending a marketing authorization for 5-aminolaevulinic acid for treatment of actinic keratosis of mild to moderate intensity on the face and scalp. The active substance is a sensitizer used in photodynamic/radiation therapy (ATC code L01XD04). The gel should cover the lesions and approximately 5 mm of the surrounding area with a film of about 1 mm thickness. The entire treatment area should be illuminated with a red light source, either with a narrow spectrum around 630 nm and a light dose of approximately 37 J/cm2 or a broader and continuous spectrum in the range between 570 and 670 nm with a light dose between 75 and 200 J/cm2. One session of photodynamic therapy should be administered for single or multiple lesions. Non- or partially responding lesions should be retreated in a second session 3 months after the first treatment. 5-aminolaevulinic acid is metabolized to protoporphyrin IX, a photoactive compound which accumulates intracellularly in the treated actinic keratosis lesions. Protoporphyrin IX is activated by illumination with red light of a suitable wavelength and energy. In the presence of oxygen, reactive oxygen species are formed which causes damage of cellular components and eventually destroys the target cells. The benefit with 5-aminolaevulinic acid is its ability to improve the complete response rate of actinic keratosis lesions. The most common side effects are reactions at the site of application. The objective of this article is to summarize the scientific review of the application. The detailed scientific assessment report and product information, including the summary of product characteristics (SmPC), are available on the EMA website (www.ema.europa.eu).